Thermoplastic resin composition for plating, resin molded product and plated part

A thermoplastic resin composition with controlled vinyl cyanide monomer and metal oxide content, combined with a rubber-containing graft copolymer and specific resins, addresses plating defects in ABS resin products, ensuring strong adhesion and appearance stability through thermal cycles, and supports environmentally friendly production.

JP7605239B2Active Publication Date: 2024-12-24TECHNO UMG CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2023062220
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2023-04-06
Publication Date
2024-12-24
Estimated Expiration
2043-04-06

AI Technical Summary

Technical Problem

Existing thermoplastic resin compositions used for plating on ABS resin molded products suffer from defects such as spots and uneven plating, poor adhesion strength after heating and cooling cycles, and poor plating appearance, which can impair the quality and functionality of the final product.

Method used

A thermoplastic resin composition with a specific vinyl cyanide monomer content in the acetone soluble component, rubber-containing graft copolymer, and controlled metal oxide content, along with AS resin and aromatic polycarbonate resin, to enhance plating film adhesion and appearance.

Benefits of technology

The composition achieves a plating film with excellent adhesion strength and appearance, even after thermal cycles, reducing defects and enabling weight reduction of plated parts while utilizing recycled materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007605239000001
    Figure 0007605239000001
  • Figure 0007605239000002
    Figure 0007605239000002
Patent Text Reader

Abstract

To provide a thermoplastic resin composition which has no poor appearance (especially, particles and uneven plating) in a plated film, is excellent in plating property and high adhesion strength, and can hold excellent plating appearance even after cold / heat cycles, regardless of the plated film's thickness or the site of its formation.SOLUTION: A thermoplastic resin composition for plating contains 10 to 50 pts.mass of a rubber-containing graft copolymer (A) obtained by graft polymerization of 20 to 70 mass% of a vinyl-based monomer mixture (a2) containing an aromatic vinyl-based monomer and a vinyl cyanide-based monomer to 30 to 80 mass% of a rubbery polymer (a1), and 50 to 90 pts.mass of other resin, in 100 pts.mass of a resin component. The content of the vinyl cyanide-based monomer in an acetone-soluble part contained in the thermoplastic resin composition is 20 to 40 mass% in the total acetone-soluble part. The content of metal oxide (D) in the thermoplastic resin composition is 4,500 ppm or less.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a thermoplastic resin composition that is free of appearance defects (particularly bumps and uneven plating) in the plating film regardless of the thickness of the plating film or the location where it is formed, has excellent plating film formability (which may be referred to as plating property, electrodeposition property, or covering property in the present invention), forms a plating film with high adhesive strength, and can retain an excellent plating appearance even after thermal cycles; and a resin molded product thereof; and a plated part using the resin molded product. [Background technology]

[0002] Molded products made from ABS resin have excellent impact resistance, mechanical strength, and chemical resistance, and are therefore used in a wide range of fields, including office equipment, information and communication equipment, electronic and electrical equipment, home appliances, automobiles, and construction. In addition, molded products made from ABS resin are also used in a wide variety of applications as plastic plated parts, as they have the characteristics of excellent plating appearance, high plating film adhesion strength, and excellent thermal cycle properties when plated to create plated products.

[0003] The plating characteristics of plated plastic parts are easily affected by factors such as the properties of the resin composition that forms the molded product and the molding conditions, and even when a resin composition containing ABS resin is used, poor plating appearance may occur. A thermoplastic resin composition that has improved plating properties through the use of a specified graft copolymer and oligomer content has been proposed as a thermoplastic resin composition that provides a plating film with high adhesion strength and suppresses swelling of the plating film and loss of adhesion strength during thermal cycles (Patent Document 1). However, even with this thermoplastic resin composition, there are problems such as the inability to form a plating film in the required locations; even if a plating film can be formed, the appearance is poor; and even if the initial adhesion strength of the plating film is high, the adhesion strength decreases after thermal cycling, which may impair the quality and even the function of the final product. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2020-158706 A Summary of the Invention [Problem to be solved by the invention]

[0005] The present invention aims to provide a thermoplastic resin composition which is free from defects in the appearance of the plating film (particularly bumps and uneven plating) regardless of the thickness of the plating film or the location where it is formed, has excellent plating properties, forms a plating film with high adhesion strength, and can retain an excellent plating appearance even after thermal cycles, and also provides a resin molded product and plated part thereof. [Means for solving the problem]

[0006] As a result of extensive investigations aimed at solving the above-mentioned problems, the present inventors have found that the above-mentioned problems can be solved by setting the content of the vinyl cyanide monomer component in the acetone soluble matter in the thermoplastic resin composition within a predetermined range and setting the content of the metal oxide to a predetermined value or less. The present invention has been achieved based on these findings, and has the following gist.

[0007] [1] In 100 parts by mass of the resin component, 10 to 50 parts by mass of a rubber-containing graft copolymer (A) obtained by graft polymerizing 30 to 80% by mass of a rubber polymer (a1) with 20 to 70% by mass of a vinyl monomer mixture (a2) containing an aromatic vinyl monomer and a vinyl cyanide monomer (wherein the total of the rubber polymer (a1) and the vinyl monomer mixture (a2) is 100% by mass); A thermoplastic resin composition comprising 50 to 90 parts by mass of other resins, the content of a vinyl cyanide monomer component in an acetone soluble matter contained in the thermoplastic resin composition is 20 to 40 mass% of the total acetone soluble matter; The thermoplastic resin composition has a metal oxide (D) content of 4500 ppm or less. [2] The thermoplastic resin composition according to [1], wherein the other resins include an AS-based resin (B) and / or an aromatic polycarbonate resin (C).

[0008] [3] The thermoplastic resin composition according to [1] or [2], wherein the other resins include a recycled resin (E).

[0009] [4] A resin molded product obtained by molding the thermoplastic resin composition according to any one of [1] to [3].

[0010] [5] A plated part in which plating is applied to part or the entirety of the resin molded product described in [4]. Effect of the Invention

[0011] According to the thermoplastic resin composition of the present invention, it is possible to form a plating film on a resin molded article made of this thermoplastic resin composition, which has excellent plating properties and high adhesion strength, and is free of appearance defects (particularly bumps and uneven plating) regardless of the thickness of the plating film or the location where it is formed, even after thermal cycling. For this reason, even a thin plating film can be made to have excellent appearance, adhesion strength, and durability against thermal cycles, making it possible to reduce the weight of plated parts without compromising decorativeness, as well as shortening the plating process time and reducing the incidence of defective products. It is also possible to make effective use of recycled resins, enabling environmentally friendly product designs. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS The present invention will be described in detail below with reference to the preferred embodiments. In the present invention, the "molded resin article" is an article obtained by molding the thermoplastic resin composition of the present invention. The term "plated part" refers to a resin molded product that has been subjected to a plating treatment, and has a plating film on at least a portion of the surface of the resin molded product. In the present invention, the term "plating ability" refers to electrodeposition ability and covering ability based on the "formability of a plating film" and the "properties of the formed plating film". The symbol "~" indicating a range of numerical values ​​means that the numerical values ​​before and after it are included as the lower limit and upper limit.

[0013] [Thermoplastic resin composition] The thermoplastic resin composition of the present invention is a thermoplastic resin composition containing 10 to 50 parts by mass of a rubber-containing graft copolymer (A) (hereinafter, sometimes referred to as "component (A)") obtained by graft polymerizing 30 to 80 mass% of a rubber polymer (a1) with 20 to 70 mass% of a vinyl monomer mixture (a2) containing an aromatic vinyl monomer and a vinyl cyanide monomer (wherein the total of the rubber polymer (a1) and the vinyl monomer mixture (a2) is 100 mass%) in 100 parts by mass of a resin component, and 50 to 90 parts by mass of other resins, characterized in that the content of the vinyl cyanide monomer component in the acetone soluble matter contained in the thermoplastic resin composition is 20 to 40 mass% of the total acetone soluble matter, and the content of a metal oxide (D) in the thermoplastic resin composition is 4500 ppm or less.

[0014] [Rubber-containing graft copolymer (A)] The rubber-containing graft copolymer (A) is obtained by graft polymerizing a vinyl monomer mixture (a2) in the presence of a rubber polymer (a1).

[0015] <Rubber polymer (a1)> The rubber-like polymer (a1) (hereinafter, sometimes referred to as "component (a1)") constituting the rubber-containing graft copolymer (A) is not particularly limited, but examples thereof include diene-based rubber, acrylic rubber, and ethylene-based rubber, and specifically includes polybutadiene, poly(butadiene-styrene), poly(butadiene-acrylonitrile), polyisoprene, poly(butadiene-butyl acrylate), poly(butadiene-methyl acrylate), polybutyl acrylate, poly(butadiene-methyl methacrylate), poly(butadiene-ethyl acrylate), ethylene-propylene rubber, ethylene-propylene-diene rubber, poly(ethylene-isobutylene), poly(ethylene-methyl acrylate), and poly(ethylene-ethyl acrylate). These rubber-like polymers are used alone or in a mixture of two or more kinds. Among these, polybutadiene, poly(butadiene-styrene), poly(butadiene-acrylonitrile), poly(butadiene-butyl acrylate), and poly(butadiene-methyl acrylate) are preferred, and polybutadiene and poly(butadiene-styrene) are more preferably used because the thermoplastic resin composition of the present invention has excellent impact resistance and plating ability.

[0016] The volume average particle diameter of the rubber polymer (a1) is preferably 50 to 500 nm, more preferably 150 to 400 nm, even more preferably 250 to 340 nm, and most preferably 270 to 330 nm, from the viewpoints of impact resistance, fluidity, and plating property of the resulting thermoplastic resin composition. The volume average particle size of the rubber polymer (a1) is a value measured by the method described in the Examples section below. The volume average particle size of the rubber polymer (a1) may be measured when it is used, or can be confirmed by image analysis using an electron microscope photograph of the resin composition.

[0017] <Vinyl monomer mixture (a2)> The vinyl monomer mixture (a2) (hereinafter sometimes referred to as "component (a2)") is a vinyl monomer mixture containing at least an aromatic vinyl monomer and a vinyl cyanide monomer.

[0018] Examples of aromatic vinyl monomers include styrene, α-methylstyrene, p-methylstyrene, vinyltoluene, t-butylstyrene, o-ethylstyrene, o-chlorostyrene, and o,p-dichlorostyrene, with styrene and α-methylstyrene being particularly preferred. The aromatic vinyl monomers may be used alone or in combination of two or more.

[0019] Examples of the vinyl cyanide monomer include acrylonitrile, methacrylonitrile, ethacrylonitrile, etc., with acrylonitrile being particularly preferred. The vinyl cyanide monomer may be used alone or in combination of two or more.

[0020] The ratio of the aromatic vinyl monomer and the vinyl cyanide monomer in 100% by mass of the vinyl monomer mixture (a2) is preferably aromatic vinyl monomer / vinyl cyanide monomer=60-80% by mass / 20-40% by mass, more preferably 65-80% by mass / 20-35% by mass, and even more preferably 67-76% by mass / 24-33% by mass, from the viewpoints of moldability of the resulting thermoplastic resin composition and appearance of the molded product.

[0021] The vinyl monomer mixture (a2) may contain, in addition to the aromatic vinyl monomer and the vinyl cyanide monomer, other vinyl monomers copolymerizable therewith in the range of 0 to 30 mass%. Examples of other vinyl monomers copolymerizable therewith include, but are not limited to, one or more of unsaturated carboxylic acid ester monomers such as methyl (meth)acrylate, maleimide monomers such as N-methylmaleimide, N-cyclohexylmaleimide, and N-phenylmaleimide, unsaturated dicarboxylic acids such as maleic acid, unsaturated dicarboxylic anhydrides such as maleic anhydride, and unsaturated amides such as acrylamide. Among these, methyl (meth)acrylate, N-phenylmaleimide, and maleic anhydride are preferred. Note that "(meth)acrylic acid" refers to either or both of acrylic acid and methacrylic acid.

[0022] <Ratio of rubber polymer (a1) and vinyl monomer mixture (a2)> The rubber-containing graft copolymer (A) is obtained by graft polymerizing 20 to 70 mass % of a vinyl monomer mixture (a2) in the presence of 30 to 80 mass % of a rubber polymer (a1), where the total of the rubber polymer (a1) and the vinyl monomer mixture (a2) is 100 mass %. If the rubber polymer (a1) is less than 30% by mass and the vinyl monomer mixture (a2) is more than 70% by mass, the thermoplastic resin composition obtained tends to have poor impact resistance, whereas if the rubber polymer (a1) is more than 80% by mass and the vinyl monomer mixture (a2) is less than 20% by mass, the impact resistance and moldability tend to decrease. The proportion of the rubber polymer (a1) is preferably 35-70% by mass, more preferably 40-65% by mass, and the proportion of the vinyl monomer mixture (a2) is preferably 30-65% by mass, more preferably 35-60% by mass.

[0023] The rubber-containing graft copolymer (A) does not need to be entirely grafted with the vinyl monomer mixture (a2), and is usually used as a mixture with a non-grafted copolymer. This mixture is essentially a composition, but in the present invention, it is included in the rubber-containing graft copolymer (A). The non-grafted copolymer is a component extracted as an acetone soluble component.

[0024] <Grafting rate> The graft ratio of the rubber-containing graft copolymer (A) is not limited, but from the viewpoint of impact resistance, it is preferably from 10 to 150% by mass, more preferably from 20 to 120% by mass, and even more preferably from 30 to 90% by mass. The graft ratio of the rubber-containing graft copolymer (A) is measured by the method described in the Examples section below.

[0025] <Molecular weight of ungrafted copolymer> The composition of the non-grafted copolymer in the rubber-containing graft copolymer (A), i.e., the acetone-soluble portion of the rubber-containing graft copolymer (A), falls within the range of the blending ratio of the monomer component, i.e., the vinyl monomer mixture (a2). The mass average molecular weight (Mw) of the ungrafted copolymer is preferably 20,000 to 400,000, more preferably 30,000 to 200,000, and even more preferably 40,000 to 100,000. The molecular weight distribution (Mw / Mn) is preferably 2.0 to 4.0, more preferably 2.5 to 3.5, and even more preferably 2.7 to 3.2. When the mass average molecular weight (Mw) and the molecular weight distribution (Mw / Mn) are within the above ranges, the fluidity and impact resistance of the obtained thermoplastic resin composition tend to be more excellent. Here, the mass average molecular weight (Mw) and molecular weight distribution (Mw / Mn) of the ungrafted copolymer (acetone soluble portion) can be measured as polystyrene equivalent values ​​by GPC, as described in detail in the Examples section below.

[0026] <Graft polymerization method> The method of graft polymerization of the rubber-containing graft copolymer (A) is not particularly limited, and the rubber-containing graft copolymer (A) can be produced by any method such as a known emulsion polymerization method, suspension polymerization method, continuous bulk polymerization method, continuous solution polymerization method, etc. In particular, the emulsion polymerization method is preferred in terms of ease of handling (e.g., easy adjustment of the rubber content of the rubber-containing graft copolymer (A)), extremely little generation of oligomers derived from the grafted monomer, no organic solvent such as toluene or benzene is used, and no residues of these, as well as easy adjustment of the rubber content, product safety, etc.

[0027] In the process of production by emulsion polymerization, examples of the coagulant used when recovering from the emulsion state include metal salts such as calcium chloride, calcium acetate, and aluminum sulfate, and inorganic acids such as sulfuric acid, hydrochloric acid, phosphoric acid, and nitric acid. Among these, a graft copolymer recovered using an inorganic acid is preferable. This reduces the effects of deterioration and discoloration of the thermoplastic resin composition, as well as the adhesion strength of the plating, and allows the performance of the final part to be maintained for a particularly long period of time. The coagulant is selected depending on the emulsifier, but when a carboxylic acid soap such as a fatty acid soap or a rosin acid soap is used as the emulsifier, either coagulant can be used for recovery, so it is preferable to coagulate and recover using an inorganic acid, especially sulfuric acid. However, if the product is coagulated with sulfuric acid and then neutralized with sodium hydroxide, etc., it is difficult to obtain the performance required for the final part, so only rinsing with water is sufficient. The amount of the coagulant added is usually 1 to 5 parts by mass, preferably 2 to 4 parts by mass, per 100 parts by mass of the polymer latex. The coagulant is usually used in the form of a solution diluted to 1% to 20%. The temperature during coagulation can be set appropriately, but is usually in the range of 50 to 95°C.

[0028] The rubber-containing graft copolymer (A) may be used alone, or, depending on the purpose, multiple rubber-containing graft copolymers produced separately, such as those containing different types of rubber polymers, different rubber particle sizes, or different compositions of the graft copolymer components, may be blended and used.

[0029] <Content of rubber-containing graft copolymer (A)> In the thermoplastic resin composition of the present invention, the content of component (A) in 100 parts by mass of the total of component (A) and other resin components is 10 to 50 parts by mass, preferably 12 to 45 parts by mass, more preferably 15 to 40 parts by mass, and even more preferably 20 to 35 parts by mass. When the content of component (A) is equal to or more than the lower limit, the impact resistance and plating property are good, and when it is equal to or less than the upper limit, the moldability and adhesion strength of the plating film are good.

[0030] <Rubber polymer (a1) content> The content of the rubber polymer (a1) in 100% by mass of the thermoplastic resin composition of the present invention is preferably 8 to 40% by mass, more preferably 10 to 30% by mass, and further preferably 12 to 20% by mass. If the content of the rubber polymer (a1) is equal to or more than the lower limit, the impact resistance is good, and if it is equal to or less than the upper limit, the moldability is excellent and the plating property of large molded products is also suitable.

[0031] [Other resins] The other resins used in the present invention may be thermoplastic resins, and are not particularly limited, but may include, for example, one or more of polyvinyl chloride resins, polystyrene resins, AS-based resins, polymethyl methacrylate resins, methyl methacrylate-styrene copolymer resins, methyl methacrylate-N-phenylmaleimide copolymer resins, aromatic polycarbonate resins, polyamide resins, polyester-based resins such as polyethylene terephthalate resins and polybutylene terephthalate resins, polyphenylene ether-polystyrene composite resins, polypropylene resins and polyethylene resins, olefin-based resins such as styrene-maleic anhydride copolymer resins, polyphenylene ether-based resins, polyoxymethylene-based resins, polysulfone-based resins, polyacrylate-based resins, polyphenylene-based resins, thermoplastic polyurethanes, polylactic acid, and bioplastics derived from plants. Among these, the AS-based resins (B) and aromatic polycarbonate resins (C), which will be described later, are particularly preferred as impact resistance and plating materials. Moreover, the other resin may be a resin (E) recycled from a resin molded article containing these thermoplastic resins.

[0032] In the thermoplastic resin composition of the present invention, the content of the other resins in 100 parts by mass of the total of the resin components consisting of component (A) and the other resins is 50 to 90 parts by mass, preferably 55 to 88 parts by mass, more preferably 60 to 85 parts by mass, and even more preferably 65 to 80 parts by mass. If the content of the other resins is equal to or less than the upper limit, the impact resistance and plating property are good, and if it is equal to or more than the lower limit, the adhesion strength of the plating film after thermal cycles is good.

[0033] [AS resin (B)] The AS resin (B) (hereinafter sometimes referred to as "component (B)") is a copolymer obtained by copolymerizing a vinyl monomer mixture (b1) containing a vinyl cyanide monomer and an aromatic vinyl monomer.

[0034] Examples of the vinyl cyanide monomer include acrylonitrile, methacrylonitrile, and ethacrylonitrile, with acrylonitrile being particularly preferred. The vinyl cyanide monomer may be used alone or in combination of two or more. Examples of aromatic vinyl monomers include styrene, α-methylstyrene, p-methylstyrene, vinyltoluene, t-butylstyrene, o-ethylstyrene, o-chlorostyrene, and o,p-dichlorostyrene, with styrene and α-methylstyrene being particularly preferred. The aromatic vinyl monomers may be used alone or in combination of two or more.

[0035] The ratio of the vinyl cyanide monomer and the aromatic vinyl monomer in 100 mass% of the vinyl monomer mixture (b1) is, from the viewpoint of moldability and plating property of the obtained thermoplastic resin composition, vinyl cyanide monomer / aromatic vinyl monomer=20 to 40 mass% / 60 to 80 mass%, preferably 22 to 38 mass% / 62 to 78 mass%, more preferably 24 to 35 mass% / 65 to 76 mass%, further preferably 25 to 32 mass% / 68 to 75 mass%, and most preferably 25 to 29 mass% / 71 to 75 mass%.

[0036] The vinyl monomer mixture (b1) may contain, in addition to the vinyl cyanide monomer and the aromatic vinyl monomer, other vinyl monomer units copolymerizable therewith in the range of 0 to 30 mass%. Examples of the other vinyl monomers copolymerizable therewith include, but are not limited to, one or more of unsaturated carboxylic acid ester monomers such as methyl (meth)acrylate, maleimide monomers such as N-methylmaleimide, N-cyclohexylmaleimide, and N-phenylmaleimide, unsaturated dicarboxylic acids such as maleic acid, unsaturated dicarboxylic anhydrides such as maleic anhydride, and unsaturated amides such as acrylamide. Among these, methyl (meth)acrylate, N-phenylmaleimide, and maleic anhydride are preferred.

[0037] The mass average molecular weight (Mw) of the AS resin (B) is preferably 50,000 to 300,000, more preferably 65,000 to 200,000, and further preferably 80,000 to 150,000. The molecular weight distribution (Mw / Mn) is preferably 1.3 to 2.8, more preferably 1.8 to 2.6, and further preferably 1.7 to 2.4. Here, the mass average molecular weight and the molecular weight distribution (Mw / Mn) of the AS resin (B) can be measured as polystyrene equivalent values ​​by GPC, as described in detail in the Examples section below.

[0038] The AS resin (B) may be used alone or in combination of two or more types having different monomer compositions, molecular weights, etc.

[0039] The manufacturing method of the AS resin (B) is not particularly limited, and examples thereof include bulk polymerization, solution polymerization, suspension polymerization, and emulsion polymerization. If volatile components or oligomers are generated during the manufacturing process, they are likely to cause defects in appearance such as silver when molding resin molded products, and measures to prevent defective products from being generated are required, such as degassing the molding die and cleaning the die. In particular, since oligomers are likely to be generated in bulk polymerization and solution polymerization, for example, JP-A-53-19397 discloses a method for reducing oligomers. This makes it difficult for silver and dirt to appear on molded products, and it is also possible to reduce the impact on subsequent plating processes of secondary processing, but if the suspension polymerization or emulsion polymerization method is used, in which oligomer generation is so small that it is not detectable, the phenomenon of defects due to oligomers does not occur. Note that, when the blending amount is large, the suspension polymerization method is preferable because the emulsion polymerization method causes deterioration of thermal stability (discoloration due to heat) due to the influence of the emulsifier.

[0040] [Aromatic polycarbonate resin (C)] The aromatic polycarbonate resin (C) (hereinafter sometimes referred to as "component (C)") is not particularly limited, but one having a viscosity average molecular weight (Mv) of 10,000 to 100,000, particularly 15,000 to 30,000 is preferably used. When the viscosity average molecular weight (Mv) of the aromatic polycarbonate resin (C) is within the above range, the impact resistance and moldability of the obtained molded article are more excellent.

[0041] Here, the viscosity average molecular weight (Mv) of the aromatic polycarbonate resin (C) is measured using an Ubbelohde viscometer in a solution containing methylene chloride as a solvent, and calculated using the following Schnell viscosity formula. [η]=1.23×10 -4 Mv 0.83 (In the formula, η represents the intrinsic viscosity, and Mv represents the viscosity average molecular weight.)

[0042] Such an aromatic polycarbonate resin (C) is usually produced by reacting a dihydric phenol with a carbonate precursor by a solution method or a melting method. The dihydric phenol used here is 2,2-bis(4-hydroxyphenyl)propane (bisphenol A), but it may be partially or completely replaced with another dihydric phenol. Examples of other dihydric phenols include bis(4-hydroxyphenyl)methane, 1,1-bis(4-hydroxyphenyl)ethane, 2,2-bis(4-hydroxy-3,5-dimethylphenyl)propane, and bis(4-hydroxyphenyl)sulfone. Examples of carbonate precursors include carbonyl halides, carbonyl esters, and haloformates, and specifically, for example, phosgene, diphenyl carbonate, dihaloformates of dihydric phenols, and mixtures thereof.

[0043] In producing the aromatic polycarbonate resin (C), a suitable molecular weight regulator, branching agent, catalyst for promoting the reaction, etc. may also be used.

[0044] In the present invention, two or more kinds of aromatic polycarbonate resins thus produced may be mixed and used. For example, two or more kinds of aromatic polycarbonate resins having different viscosity average molecular weights (Mv) may be mixed and adjusted to the above-mentioned suitable viscosity average molecular weight (Mv) for use.

[0045] [Metal oxide (D)] The metal oxide (D) in the present invention is not particularly limited, and examples thereof include titanium oxide, zinc oxide, zinc sulfide, magnesium oxide, aluminum oxide, barium oxide, calcium oxide, molybdenum oxide, antimony compounds (antimony trioxide), and further composite oxides thereof, such as titanium / antimony composite oxide, nickel / titanium / antimony composite oxide, etc. In the examples shown below, titanium oxide, nickel / titanium / antimony composite oxide, and magnesium oxide are evaluated, but the metal oxide (D) according to the present invention may be any metal oxide and is not limited thereto. The thermoplastic resin composition of the present invention may contain only one kind of these metal oxides (D), or may contain two or more kinds.

[0046] These metal oxides (D) are derived from colorants, and resin stabilizers and modifiers and are mixed into the thermoplastic resin composition.

[0047] The average primary particle size of these metal oxides (D) is preferably within the range of 0.01 to 10 μm, more preferably 0.05 to 1 μm, and even more preferably 0.1 to 0.5 μm, since if it is too small or too large, it may affect plating properties. The average primary particle size of the metal oxide (D) can be calculated as the average of the long axis and the short axis of each of 50 randomly selected particles observed under an electron microscope and measured by magnified image analysis.

[0048] In the thermoplastic resin composition of the present invention, the content of the metal oxide (D) needs to be adjusted to 4500 ppm or less. If the content of the metal oxide (D) exceeds 4500 ppm, the appearance and plating properties of the plating film are impaired. The content of the metal oxide (D) in the thermoplastic resin composition of the present invention is preferably 4000 ppm or less, more preferably 3000 ppm or less, even more preferably 2000 ppm or less, and particularly preferably 1500 ppm or less, and more preferably 1000 ppm or less, 600 ppm or less, 300 ppm or less, and 200 ppm or less in that order. The lower limit of the content of the metal oxide (D) in the thermoplastic resin composition is not particularly limited, and may be 0 ppm, i.e., no metal oxide (D) may be contained. Among the particularly small ranges, the metal oxide (D) may be contained in an amount of more than 0 ppm, such as 0.01 ppm or more, 0.05 ppm or more, 0.1 ppm or more, or 0.5 ppm or more. From the viewpoint of plating property, the lower the content of the metal oxide (D), the better, but if the content of the metal oxide (D) is 200 ppm or less, no significant difference is observed in plating property, etc.

[0049] In order to keep the content of metal oxide (D) in the thermoplastic resin composition below the above upper limit, there can be mentioned methods for preventing the inclusion of metal oxide in the production process of the rubber-containing graft copolymer (A) and other resins, and for controlling the content of metal oxide (D) in the thermoplastic resin composition by adjusting the amount of additives containing metal oxide or, when a resin containing metal oxide is used as the recycled resin (E) described below, the amount of the additives containing metal oxide or the resin containing metal oxide is used.

[0050] The method for measuring the content of the metal oxide (D) in the thermoplastic resin composition of the present invention is as described in the Examples section below, but it can also be calculated from the metal oxide (D) content of each component used in preparing the thermoplastic resin composition. As a method of measurement by analysis, for example, in analysis by a fluorescent X-ray device, a calibration curve of the content and intensity according to the type of metal oxide is prepared from a sample with a known content in advance, and a thermoplastic resin composition sample is measured by the fluorescent X-ray device, and the content can be obtained from the measured intensity. Also, the content of the metal oxide can be obtained by an infrared spectroscopic analyzer (IR) by preparing a calibration curve of the type and content of the metal oxide. In particular, when the metal oxide content of the sample is small, the polymer components and non-polymer components in the sample can be separated using a solvent or the like, and the metal oxide content of the component from which the polymer components have been removed as much as possible can be analyzed using an X-ray fluorescence analyzer or an infrared spectroscopic analyzer. These measurement methods can also be used to analyze the metal oxide content of recycled materials, etc.

[0051] [Recycled resin (E)] In the present invention, as the other resin, a recycled resin (E) (hereinafter, sometimes referred to as "recycled resin (E)" or "component (E)"), for example, a recycled ABS resin, a recycled AS resin, or a recycled aromatic polycarbonate resin, can be blended. The recycled resin (E) may be a post-consumer product or a pre-consumer product, and the supply source thereof is not limited.

[0052] In the present invention, when a recycled resin (E) is used as the other resin, it is preferable to check at the raw material stage so that the content of metal oxide (D) in the finally obtained thermoplastic resin composition containing recycled resin (E) is not more than the above upper limit and the content of vinyl cyanide monomer components in the acetone soluble matter is within the following range. Moreover, if the content is outside these ranges, the rubber-containing graft copolymer (A), AS-based resin (B) and aromatic polycarbonate resin (C) can be added again to adjust the content so as to fall within the limits, thereby enabling environmentally friendly production without generating waste of recycled resin (E).

[0053] [Vinyl cyanide monomer content in acetone solubles] The thermoplastic resin composition of the present invention is characterized in that the content of the vinyl cyanide monomer component in the acetone soluble matter contained in the thermoplastic resin composition is 20 to 40 mass% of the total acetone soluble matter. When the content of the vinyl cyanide monomer component in the acetone soluble matter is in this range, the thermoplastic resin composition has excellent plating properties. From the viewpoint of plating properties, the content of the vinyl cyanide monomer component in the total acetone soluble matter is preferably 21 to 35 mass %, more preferably 22 to 33 mass %, and further preferably 24 to 30 mass %. The content of the vinyl cyanide monomer component in the acetone soluble matter can be determined by a method of direct extraction measurement, such as the method described in the Examples section below, or by a method of calculation from the acetone soluble matter of the raw material used.

[0054] <Molecular weight of acetone soluble matter> The mass average molecular weight (Mw) of the acetone soluble matter in the thermoplastic resin composition of the present invention is preferably 20,000 to 400,000, more preferably 30,000 to 200,000, and further preferably 40,000 to 180,000. When the mass average molecular weight (Mw) is within the above range, the thermoplastic resin composition of the present invention tends to have better fluidity and impact resistance. Here, the mass average molecular weight (Mw) of the acetone soluble matter in the thermoplastic resin composition can be measured as a polystyrene equivalent value by GPC, the details of which are as described in the Examples section below.

[0055] [Additives] The thermoplastic resin composition of the present invention may contain additives that are typically blended into thermoplastic resin compositions, if necessary. Examples of additives include colorants such as pigments and dyes, fillers (carbon black, silica, etc.), halogen-based flame retardants, phosphorus-based flame retardants, stabilizers, reinforcing agents, processing aids, heat resistance agents, antioxidants, weather resistance agents, release agents, plasticizers, and antistatic agents. However, it is preferable to use additives that do not contain metal oxides or that contain only a small amount of metal oxides, so that the content of metal oxide (D) in the thermoplastic resin composition after blending such additives is not more than the above upper limit.

[0056] [Method of producing thermoplastic resin composition] The thermoplastic resin composition of the present invention can be produced by mixing and dispersing the component (A) and other resins such as an AS-based resin (B), an aromatic polycarbonate resin (C), and a recycled resin (E) together with various additives used as necessary using a V-type blender, a Henschel mixer, or the like, and melt-kneading the mixture thus obtained using a kneading machine such as an extruder, a Banbury mixer, a pressure kneader, or a roll, and then cutting and pelletizing the mixture using a pelletizer, or the like. The thermoplastic resin composition of the present invention is molded into the resin molded article of the present invention.

[0057] [Uses of thermoplastic resin compositions] The thermoplastic resin composition of the present invention is excellent in moldability and physical properties, and is also suitable for secondary processing such as plating, painting, and silk printing, and is particularly effective in plating applications.

[0058] [Resin molded product] The resin molded article of the present invention is obtained by molding the thermoplastic resin composition of the present invention, and has excellent impact strength and moldability, as well as excellent appearance of the plating film and plating properties. In addition, by adjusting the type and amount of other resins used in combination with the rubber-containing graft copolymer (A), it is possible to provide a composition having excellent mechanical properties such as rigidity and excellent heat resistance.

[0059] Examples of methods for molding the thermoplastic resin composition of the present invention include injection molding, injection compression molding, extrusion, blow molding, vacuum molding, pressure molding, calendar molding, inflation molding, gas injection molding, etc. Among these, injection molding is preferred because it is suitable for mass production and can produce molded products with high dimensional accuracy.

[0060] [Plated parts] The plated part of the present invention is obtained by plating all or part of the above-mentioned resin molded article of the present invention, and has the resin molded article of the present invention and a plating film formed on at least a part of the surface of the resin molded article.

[0061] The plated part of the present invention can be obtained by subjecting the resin molded article of the present invention to a plating treatment. The plating method is not limited in any way. Examples of the plating method include an electroless plating method, a direct plating method, and a non-chromium plating method.

[0062] The plated part of the present invention exerts sufficient effects in the plating conductor process, has excellent appearance, and further has excellent conductive film formability, so that it is possible to provide an excellent part that exerts effects even when the plating film is thin. This contributes to weight reduction, and also has environmentally friendly effects such as shortening plating processing time, reducing the rate of defective products, and making effective use of recycled resources. Furthermore, as an additional effect, since the plated part of the present invention uses the resin molded product of the present invention, it has excellent adhesion strength with the plating film, excellent thermal cycle resistance, retains the adhesion of the plating film after thermal cycles, and has excellent plating appearance.

[0063] [Possible uses and applications] The specific applications of the plated parts of the present invention are diverse, and they are suitable for a wide range of applications, such as industrial products such as automobiles, electrical, electronic and mechanical parts, information and communication devices, and water-washing parts, as well as sports, leisure, games and decorative items, office supplies, and daily necessities. Specific examples of automotive applications include radiator grilles, door handles, emblems, lamp housings, various moldings and garnishes, and wheel caps. Electrical applications include various switch buttons, arm handles, refrigerator door handles, mobile phone parts, and various housings. Applications for flushing parts include various flushing handle shower heads and water outlets. Examples of applications include sports, leisure, games, decorative items, and daily necessities, such as pachinko machines, pachinko slot machines, watch frames, decorative buttons, and cosmetic caps. Among these, the plated parts of the present invention are preferably used for automobile exterior and interior parts, water-washed parts, etc. EXAMPLES

[0064] In order to more specifically explain the present invention, the following examples and comparative examples are given, but the present invention is not limited to these examples. In addition, "%" means "% by mass" and "parts" means "parts by mass" unless otherwise specified. In addition, in some places, acrylonitrile is abbreviated as "AN", styrene as "ST", and butadiene as "BD".

[0065] In the following, the volume average particle size of the rubber polymer (a1) was measured by the following (1), and the graft ratio of the rubber-containing graft copolymer (A) was measured by the following (2). The content of vinyl cyanide monomer components in the acetone soluble matter in the thermoplastic resin composition was measured by the following (3). The contents of vinyl cyanide monomer components in the acetone soluble matter (ungrafted copolymer) of the rubber-containing graft copolymer (A) and the acetone soluble matter of the AS-based resin (B) were also measured by the same method (3). The mass average molecular weight (Mw) and molecular weight distribution (Mw / Mn) of the acetone soluble portion (ungrafted copolymer) of the rubber-containing graft copolymer (A), the AS-based resin (B), and the recycled resin (E) were measured by the following (4). The method for measuring the viscosity average molecular weight (Mv) of the aromatic polycarbonate resin (C) is as described above. The content of the metal oxide (D) was analyzed according to the following (5).

[0066] (1) Volume average particle size The volume average particle diameter of the rubber polymer (a1) in the latex was measured at room temperature using a Honeywell Microtrac UPA150 (trade name). The unit is nm. It is known that there is no substantial difference between the latex particle diameter of the rubber polymer (a1) and the rubber particle diameter of the rubber polymer (a1) in the resin composition using the latex, and the former corresponds to the latter.

[0067] (2) Graft ratio The graft ratio of the rubber-containing graft copolymer (A) is calculated by the following formula. Graft ratio (mass%) = {[(n)-(m)×L] / [(m)×L]}×100 In the above formula, n is the mass n (g) of the acetone insoluble matter obtained by adding about 1 g (weighed weight: m (g)) of the rubber-containing graft copolymer (A) to 20 mL of acetone, shaking the mixture at 25°C for 2 hours with a shaker, and then centrifuging the mixture at 5°C for 60 minutes with a centrifuge (rotation speed: 23,000 rpm) to separate the acetone insoluble matter from the acetone soluble matter. L is the mass (g) of the rubber-like polymer (a1) contained in the rubber-containing graft copolymer (A). The mass of the rubber-like polymer (a1) can be calculated from the polymerization recipe and the polymerization conversion rate, or determined by infrared absorption spectroscopy.

[0068] (3) Content of vinyl cyanide monomer in acetone solubles For Examples 1 to 9 and Comparative Examples 1 to 6, 2 g of each of the obtained thermoplastic resin compositions was put into 40 mL of acetone, and the mixture was shaken for 2 hours with a shaker at a temperature condition of 25°C, and then stretched and separated for 60 minutes with a centrifuge (rotation speed: 23,000 rpm) at a temperature condition of 5°C to separate the acetone-soluble and acetone-insoluble components. The obtained acetone-soluble components were dropped into methanol to precipitate the polymer components, and the solid components were then filtered and extracted, and dried in a vacuum dryer for 24 hours. The nitrogen element (N) was measured using a nitrogen element analyzer: JM10 MICRO CORDER (manufactured by J-SCIENCE-LAB Co., Ltd.). The content of the vinyl cyanide monomer unit was calculated from the content of the nitrogen element (N) present in the sample, and this was taken as the content of the vinyl cyanide monomer component in the acetone-soluble components in the thermoplastic resin composition. For the measurement sample of the non-grafted copolymer of component (A), the acetone soluble portion having the above graft ratio was dropped into methanol to precipitate the polymer component, and then the solid matter extracted by filtration was dried in a vacuum dryer for 24 hours, after which the nitrogen element (N) was measured to determine the content of vinyl cyanide monomer units. For component (B), the produced component (B) was dissolved in acetone, and the polymer component was then precipitated in methanol and dried in a vacuum dryer for 24 hours. The nitrogen element (N) was then measured to determine the content of vinyl cyanide monomer units. In the case of containing an aromatic polycarbonate resin as in Examples 10 to 12 and Comparative Examples 7 to 9, the resin composition is dissolved in dichloromethane, and then the polymer component is extracted using methanol, and the polymer component is refluxed with monoethanolamine to decompose the aromatic polycarbonate resin. Then, the composition is washed with 1 / 10N hydrochloric acid, and the decomposition product is removed by repeating washing with methanol again. The remaining methanol insoluble matter is taken out and dried, and then, in the same manner as in the above-mentioned Example 1, the acetone soluble matter and the insoluble matter are separated, and the content of the vinyl cyanide monomer component in the acetone soluble matter is measured. In this example, the amount of vinyl cyanide monomer in the acetone soluble matter was calculated by multiplying the amount of the acetone soluble matter of the raw material used by the blending ratio of each component.

[0069] (4) Mass average molecular weight (Mw) and molecular weight distribution (Mw / Mn) The mass average molecular weight (Mw) and the molecular weight distribution (Mw / Mn) were measured in terms of polystyrene using GPC (GPC: Waters Corporation's "GPC / V2000", column: Showa Denko K.K.'s "Shodex AT-G+AT-806MS") and o-dichlorobenzene (145°C) as a solvent. For the measurement sample of the ungrafted copolymer, the acetone soluble portion having the above graft ratio was dropped into methanol to precipitate the polymer component, and then the solid portion was filtered and taken out, and dried in a vacuum dryer for 24 hours, and the resultant was used for the GPC measurement. In addition, for the GPC measurement of components (B) and (E), components (B) and (E) were dissolved in acetone, and then the polymer components were precipitated in methanol and dried in a vacuum dryer for 24 hours before use in the GPC measurement.

[0070] (5) Metal oxide content Using a Shimadzu Corporation energy dispersive fluorescent X-ray spectrometer (EDX-7000), a calibration curve of the content of metal oxide was prepared in advance according to the type of metal oxide, and the content of metal oxide was measured. For the recycled products (E-1) and (E-2), the acetone insoluble matter was extracted and dried, and the metal oxide content was measured using the same device.

[0071] [Rubber-containing graft copolymer (A)] <Synthesis Example 1: Production of Rubber-Containing Graft Copolymer (A-1)> In a nitrogen-substituted reactor, 125 parts of pure water, 0.5 parts of glucose, 0.5 parts of sodium pyrophosphate, 0.005 parts of ferrous sulfate, and 60 parts of polybutadiene (BR) latex (solid content equivalent) having a volume average particle size of 340 nm as a rubber polymer (a1-1) were charged, and the temperature inside the reactor was raised to 65°C while stirring. The polymerization was started when the internal temperature reached 65°C, and 30 parts of styrene (ST) and 10 parts of acrylonitrile (AN) were used as components (a2-1), and this and 0.25 parts of a t-dodecyl mercaptan mixture as a chain transfer agent were continuously added over 5 hours. At the same time, an aqueous solution consisting of cumene hydroperoxide (0.2 parts) and disproportionated rosin acid sodium salt (0.4 parts), which are polymerization initiators, was continuously added over 7 hours to complete the reaction. To the obtained latex, 1 part of 2,2'-methylenebis(4-methyl-6-t-butylphenol) was added per 100 parts of latex solid content, and then the latex (100 parts of polymer component) was coagulated using 5% sulfuric acid so that the ratio of the coagulant was 2 parts, followed by washing, filtration, and drying to obtain a powder-like rubber-containing graft copolymer (A-1). This rubber-containing graft copolymer (A-1) had a rubber (component (a1-1)) content of 59.8% and a graft ratio of 45%. In addition, the acetone soluble matter contained 24.8% vinyl cyanide monomer component, a mass average molecular weight (Mw) of 48,000, and a molecular weight distribution (Mw / Mn) of 3.1.

[0072] <Synthesis Example 2: Production of Rubber-Containing Graft Copolymer (A-2)> In a nitrogen-substituted reactor, 125 parts of pure water, 0.5 parts of glucose, 0.5 parts of sodium pyrophosphate, 0.005 parts of ferrous sulfate, and 50 parts of poly(butadiene-styrene) (SBR) latex (solid content equivalent) having a volume average particle size of 310 nm as a rubber polymer (a1-2) were charged, and the temperature inside the reactor was raised to 65°C while stirring. The polymerization was started when the internal temperature reached 65°C, and 35.5 parts of styrene (ST) and 14.5 parts of acrylonitrile (AN) were used as components (a2-2), and this and 0.20 parts of a chain transfer agent t-dodecyl mercaptan mixture were continuously added over 5 hours. At the same time, an aqueous solution consisting of cumene hydroperoxide (0.2 parts) and disproportionated rosin acid sodium salt (0.7 parts), which are polymerization initiators, was continuously added over 7 hours to complete the reaction. To the obtained latex, 1 part of 2,2'-methylenebis(4-methyl-6-t-butylphenol) was added per 100 parts of the latex solid content, and the same procedure as in Synthesis Example 1 was carried out to obtain a powdery rubber-containing graft copolymer (A2). This rubber-containing graft copolymer (A-2) had a rubber (component (a1-2)) content of 49.8% and a graft ratio of 46%. In addition, the acetone soluble matter contained 28.7% vinyl cyanide monomer component, a mass average molecular weight (Mw) of 68,000, and a molecular weight distribution (Mw / Mn) of 2.8.

[0073] <Synthesis Example 3: Production of Rubber-Containing Graft Copolymer (A-3)> In a nitrogen-substituted reactor, 125 parts of pure water, 0.5 parts of glucose, 0.5 parts of sodium pyrophosphate, 0.005 parts of ferrous sulfate, and 50 parts of polybutadiene (BD) latex with a volume average particle size of 290 nm (solid content equivalent) as a rubber polymer (a1-3) were charged, and the temperature inside the reactor was raised to 65°C while stirring. The polymerization was started when the internal temperature reached 65°C, and 37.5 parts of styrene (ST) and 12.5 parts of acrylonitrile (AN) were used as components (a2-3), and this and 0.25 parts of a t-dodecyl mercaptan mixture as a chain transfer agent were continuously added over 5 hours. At the same time, an aqueous solution consisting of cumene hydroperoxide (0.2 parts) and disproportionated rosin acid sodium salt (0.7 parts), which are polymerization initiators, was continuously added over 7 hours to complete the reaction. To the obtained latex, 1 part of 2,2'-methylenebis(4-methyl-6-t-butylphenol) was added per 100 parts of latex solid content, and then, this latex (100 parts of polymer component) was salted out with 5% calcium chloride so that the ratio of coagulant was 2 parts, followed by washing, filtration, and drying to obtain a powder-like rubber-containing graft copolymer (A-3). This rubber-containing graft copolymer (A-3) had a rubber (component (a1-3)) content of 49.9% and a graft ratio of 80%. In addition, the acetone soluble matter contained 26.9% vinyl cyanide monomer component, a mass average molecular weight (Mw) of 67,000, and a molecular weight distribution (Mw / Mn) of 3.1.

[0074] [AS resin (B)] <Synthesis Example 4: Production of AS-based resin (B-1)> A monomer mixture consisting of 120 parts of water, 0.002 parts of sodium alkylbenzenesulfonate, 0.5 parts of polyvinyl alcohol, 0.3 parts of azoisobutylnitrile, 0.62 parts of t-dodecylmercaptan, 23 parts of acrylonitrile, and 77 parts of styrene was used in a nitrogen-substituted reactor, and the temperature was raised from an initial temperature of 60° C. for 5 hours while gradually adding a portion of styrene, and then the temperature reached 120° C. After further reacting at 120° C. for 4 hours, the polymer was taken out and an AS-based resin (B-1) with acrylonitrile / styrene=23 / 77 was obtained. The resulting AS-based resin (B-1) had an acetone-soluble vinyl cyanide monomer content of 23.1%, a mass average molecular weight (Mw) of 154,000, and a molecular weight distribution (Mw / Mn) of 2.1.

[0075] <Synthesis Example 5: Production of AS-based resin (B-2)> An AS-based resin (B-2) with an acrylonitrile / styrene ratio of 27 / 73 was obtained in the same manner as in Synthesis Example 4, except that 0.55 parts of t-dodecyl mercaptan and a monomer mixture consisting of 28 parts of acrylonitrile and 72 parts of styrene were used. The resulting AS-based resin (B-2) had an acetone-soluble vinyl cyanide monomer content of 28.2%, a mass average molecular weight (Mw) of 116,000, and a molecular weight distribution (Mw / Mn) of 2.0.

[0076] <Synthesis Example 6: Production of AS-based resin (B-3)> An AS-based resin (B-3) having an acrylonitrile / styrene ratio of 35 / 65 was obtained in the same manner as in Synthesis Example 4, except that 0.65 parts of t-dodecyl mercaptan and a monomer mixture consisting of 35 parts of acrylonitrile and 65 parts of styrene were used. The resulting AS-based resin (B-3) had an acetone-soluble vinyl cyanide monomer content of 34.8%, a mass average molecular weight (Mw) of 91,000, and a molecular weight distribution (Mw / Mn) of 2.1.

[0077] [Aromatic polycarbonate resin (C)] As the aromatic polycarbonate resin (C), the following commercially available product was used. Aromatic polycarbonate resin (C-1): "S3000" manufactured by Mitsubishi Engineering Plastics Corporation (viscosity average molecular weight (Mv): 22,000)

[0078] [Metal oxide (D)] As the metal oxide (D), the following commercially available products were used. Magnesium oxide (D-1): Kyowa Mag 150 manufactured by Kyowa Chemical Industry Co., Ltd. (Average primary particle size: 4.16μm) Ti / Sb / Ni Composite Oxide (D-2): "42-401A" manufactured by TOMATEC Co., Ltd. ((Ti, Sb, Ni)O 2 , average primary particle size: 1 μm) Titanium Oxide (D-3): "TITANIX JR-405" manufactured by Teika Co., Ltd. (Titanium Dioxide, average primary particle size: 0.3 μm)

[0079] [Recycled Resin (E)] <Recycled Product of ABS Resin (E-1)> Regarding the recycled ABS resin (white) recovered from the market, upon analysis, the metal oxide content (titanium oxide) was 30,000 ppm, and regarding the resin composition, the rubber content was 13.1%, the graft ratio was 76%. Also, the vinyl cyanide monomer component in the acetone-soluble content was 25.3%, the mass average molecular weight (Mw) was 132,000, and the molecular weight distribution (Mw / Mn) was 2.4. This was used as the recycled product of ABS resin (E-1).

[0080] <Recycled Product of ABS Resin (E-2)> Regarding the recycled ABS resin (black) recovered from the market, upon analysis, the metal oxide content (titanium / antimony / nickel composite oxide) was 5,000 ppm, and regarding the resin composition, the rubber content was 14.9%, the graft ratio was 68%. Also, the vinyl cyanide monomer component in the acetone-soluble content was 23.4%, the mass average molecular weight (Mw) was 158,000, and the molecular weight distribution (Mw / Mn) was 2.6. This was used as the recycled product of ABS resin (E-2).

[0081] <Recycled Product of Aromatic Polycarbonate Resin (E-3)> The recycled aromatic polycarbonate resin recovered from discarded optical discs was used. The recovery method is as follows. The 40 optical disks were placed in a CD remover (manufactured by Japan Marcel Co., Ltd.) and immersed for 15 minutes while slowly stirring with a rod to dissolve and remove the metal parts. The aromatic polycarbonate resin disks were then washed with water and dried. This process was repeated for a total of 200 disks. The obtained disk-shaped aromatic polycarbonate resin was crushed into pieces of about 4 mm × 4 mm in size by a crusher. The viscosity average molecular weight (Mv) of this recycled aromatic polycarbonate resin (E-3) was 15,000.

[0082] [Examples 1 to 12, Comparative Examples 1 to 9] The components (A), (B), (D), and (E) shown in Tables 1 and 2 were mixed in the mixing ratios (parts) shown in the tables, and 0.2 parts of ADEKA STAB "A-60 (trade name)" (tetrakis[methylene-3-(3',5'-di-t-butyl-4'-hydroxyphenyl)propionate]methane) manufactured by ADEKA Corporation and 0.1 parts of "KAOWAX EB-G (trade name)" (ethylene-bisstearic acid amide) manufactured by Kao Corporation were further mixed and melt-kneaded in a vacuum vented twin-screw extruder (Ikegai Corporation "PCM30") with a screw diameter of 30 mm at a cylinder temperature of 200 to 260°C and a vacuum of 93.325 kPa. The mixture was taken up as strands and pelletized using a pelletizer (Sokensha Corporation "SH-type pelletizer") to obtain pellets of the thermoplastic resin composition. The mass average molecular weight (Mw) of the acetone soluble matter in the resulting thermoplastic resin composition was measured by the method described above, and the results are shown in Table 1 as "mass average molecular weight (Mw) of acetone soluble matter." In addition, the content of vinyl cyanide monomer components in the acetone soluble matter in the thermoplastic resin composition was measured by the method described above, and the results are shown in Table 1 as "content of vinyl cyanide monomer components in acetone soluble matter." The following tests were carried out using the obtained thermoplastic resin composition pellets, and the results are shown in Tables 1 and 2.

[0083] [Evaluation of fluidity: Measurement of melt volume rate (MVR)] For pellets of each thermoplastic resin composition, the MVR (cm) of the thermoplastic resin composition was measured at a temperature of 220°C and a load of 98N (10kg) in accordance with the ISO 1133 standard. 3 The MVR is an index of the fluidity of a thermoplastic resin composition, and the higher the MVR, the more excellent the fluidity.

[0084] [Preparation of evaluation specimens and test method] <Preparation of test piece (a)> Using an injection molding machine (manufactured by Shibaura Machine Co., Ltd., product name "IS55FP-1.5A"), pellets of each thermoplastic resin composition were injection molded under conditions of a cylinder temperature of 220 to 250°C and a mold temperature of 60°C to obtain a test piece (A) having a length of 80 mm, a width of 10 mm, and a thickness of 4 mm. The test piece (A) was used for measuring the Charpy impact strength.

[0085] <Impact resistance evaluation: Charpy impact strength measurement> The test piece (a) was subjected to a Charpy impact test (notched) at 23°C in accordance with ISO 179 to measure the Charpy impact strength. The higher the value, the better the impact resistance.

[0086] <Preparation of test piece (b)> The pellets of each thermoplastic resin composition were injection molded using a 75-ton injection molding machine (Japan Steel Works, Ltd., JSW-75EIIP) and a metal mold for evaluating plating adhesion strength (length 90 mm x width 50 mm x thickness 3 mm) under conditions of a cylinder temperature of 250°C, a metal mold temperature of 60°C, and an injection speed of 20 mm / sec to obtain test pieces (B).

[0087] <Plating process 1> For test piece (b), a 1 cm portion of the opposite side (lower side) of the gate was masked, and then the plate was degreased by immersing it in a 50°C CRP cleaner (Okuno Chemical Industries Co., Ltd.) for 5 minutes. The degreased plate was washed with 20°C water, and then immersed in an etching solution (chromic acid: 400 g / L, sulfuric acid: 200 cc / L) at 68°C for 10 minutes to perform etching. The etched plate was washed with 20°C water, and then immersed in a 25°C CRP reducer (Okuno Chemical Industries Co., Ltd.) for 1 minute to perform neutralization. The neutralized plate was washed with 20°C water, pre-dipped in 25°C hydrochloric acid for 1 minute, and then immersed in a 40°C CRP catalyst (Okuno Chemical Industries Co., Ltd.) for 5 minutes to perform Pd-Sn colloidal catalyst treatment. The plate after the catalysis was washed with water at 20°C, and then immersed in CRP Selector A, B (manufactured by Okuno Chemical Industries Co., Ltd.) at 45°C for 7 minutes to perform a conductive treatment, and the plate after the conductive treatment was washed with water at 20°C. Next, electrolytic copper plating was performed at 20°C for 40 minutes to deposit an electrolytic copper plating film of 30 μm thickness on the plate. After electrolytic copper plating, the plate was washed with water at 20°C, and the electrolytic copper plated plate was dried at 80°C for 2 hours to obtain plating treatment sample 1.

[0088] <Platability evaluation 1> [Appearance: Visual] The plating treatment sample 1 was visually inspected for any irregularities or defects such as bumps on the surface, and was judged according to the following criteria. ◎: No problems at all (good product) ○: Small bumps, unevenness, etc. (Can be used considering subsequent plating) △: Moderate lumps, unevenness, etc. (high possibility of defective product) ×: There are large lumps and unevenness and it is not possible to deal with it (defective product: cannot be used)

[0089] [Electrodeposition: Coverage] The surface of plating treatment sample 1 was visually inspected to see whether a conductive film of copper plating was formed with good adhesion and whether it was electrodeposited, and was judged according to the following criteria. ◎: No problems at all (good product) 〇: No electroplating in areas that have little effect on contact points, etc. (Can be used) △: 10% uncoated (uncovered, unusable) ×: 10% or more of the material is not electroplated (not covered, cannot be used)

[0090] [Adhesion strength] For plated sample 1, a 1 cm wide cut was made in the plating film from the masked area, and the plating film was peeled off vertically from the non-plated area over a load measuring device to measure its strength, and the plating adhesion strength was judged according to the following criteria. ◎: Plating adhesion strength is 12N / cm or more, which is very excellent ○: Plating adhesion strength is 9N / cm or more and less than 12N / cm, no practical problem △: Plating adhesion strength is 9N / cm or less, and can be used depending on the application.

[0091] <Plating process 2> For test piece (B), a 1 cm portion of the opposite side (lower side) of the gate was masked, and then the plate was degreased by immersing it in a 50°C CRP cleaner (Okuno Chemical Industries Co., Ltd.) for 5 minutes. The degreased plate was washed with water at 20°C, and then immersed in an etching solution (chromic acid: 400 g / L, sulfuric acid: 200 cc / L) at 68°C for 10 minutes to perform etching. The etched plate was washed with water at 20°C, and then immersed in a CRP reducer (Okuno Chemical Industries Co., Ltd.) at 25°C for 1 minute to perform neutralization. The neutralized plate was washed with water at 20°C, pre-dipped in hydrochloric acid at 25°C for 1 minute, and then immersed in a CRP catalyst (Okuno Chemical Industries Co., Ltd.) at 40°C for 5 minutes to perform Pd-Sn colloidal catalyst treatment. After the catalyst was applied, the plate was washed with water at 20° C., and then immersed in CRP Selector A, B (manufactured by Okuno Chemical Industries Co., Ltd.) at 45° C. for 7 minutes to perform a conductive treatment, and the plate after the conductive treatment was washed with water at 20° C. Next, electrolytic copper plating was performed at 20° C. for 15 minutes to deposit an electrolytic copper plating film with a thickness of 10 μm on the plate. After the copper electroplating, the plate was washed with water at 20°C, and then electroplated at 55°C for 8 minutes to deposit a nickel electroplating film with a thickness of 5 μm. After the nickel electroplating, the plate was washed with water at 20°C, and then electroplated at 45°C for 2 minutes to deposit a chrome electroplating film with a thickness of 0.3 μm. The test piece was then dried at 80°C for 2 hours. At the same time, the masking was removed to simultaneously prepare a non-plated portion to obtain plating sample 2.

[0092] <Platability evaluation 2> [Appearance: Visual] The plating treatment sample 1 was visually inspected for any irregularities or defects such as bumps on the surface, and was judged according to the following criteria. ◎: No problems at all (good product) ○: Small bumps, unevenness, etc. (Can be used considering subsequent plating) △: Moderate lumps, unevenness, etc. (high possibility of defective product) ×: There are large lumps and unevenness and it is not possible to deal with it (defective product: cannot be used)

[0093] [Appearance after thermal cycle] Plated sample 2 was subjected to eight cycles of cooling at -40°C for one hour and heating at 80°C for one hour. After that, the condition of the plating film of sample 2 was visually observed, and the appearance after the cooling and heating cycles was judged according to the following criteria. ◎: No discoloration (good condition) ○: Very slight discoloration, swelling, etc. (Can be used taking into consideration) △: Slight swelling, etc. (can be used depending on application) ×: There are large lumps and unevenness and it is not possible to deal with it (defective product, cannot be used)

[0094] [Table 1]

[0095] [Table 2]

[0096] [Consideration] The thermoplastic resin compositions of Examples 1 to 12 exhibited excellent effects in the evaluation of plating properties. In contrast, the metal oxide contents of Comparative Examples 1 to 9 exceeded the range of the present invention, and therefore there were problems with poor appearance due to bumps or unevenness, and the electrical conductivity for plating was not obtained, and the adhesive strength was not obtained.

Claims

1. In 100 parts by mass of the resin component, 10 to 50 parts by mass of a rubber-containing graft copolymer (A) obtained by graft polymerizing 30 to 80% by mass of a rubber polymer (a1) with 20 to 70% by mass of a vinyl monomer mixture (a2) containing an aromatic vinyl monomer and a vinyl cyanide monomer (wherein the total of the rubber polymer (a1) and the vinyl monomer mixture (a2) is 100% by mass); A thermoplastic resin composition for plating containing 50 to 90 parts by mass of other resin, the content of a vinyl cyanide monomer component in an acetone soluble matter contained in the thermoplastic resin composition for plating is 20 to 40 mass% of the total acetone soluble matter; The thermoplastic resin composition for plating use is characterized in that the content of a metal oxide (D) in the thermoplastic resin composition for plating use is more than 0 ppm and not more than 4,500 ppm.

2. 2. The thermoplastic resin composition for plating use according to claim 1, wherein the other resins comprise an AS-based resin (B) and / or an aromatic polycarbonate resin (C).

3. 2. The thermoplastic resin composition for plating use according to claim 1, further comprising a recycled resin (E) as the other resin.

4. 4. A resin molded product obtained by molding the thermoplastic resin composition for plating use according to claim 1.

5. A plated part, which is obtained by plating a part or the whole of the resin molded product according to claim 4.

Citation Information

Patent Citations

  • Thermoplastic resin

    JP2002256043A

  • Thermoplastic resin composition, and resin molded article and coated processed article thereof

    JP2019006920A

  • Slidable resin composition and molded body of the same

    JP2019026716A

  • Thermoplastic resin composition

    JP2020158706A